2017
DOI: 10.1016/j.jamcollsurg.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Management of Immediate Post-Endovascular Aortic Aneurysm Repair Type Ia Endoleaks and Late Outcomes

Abstract: BACKGROUND Post-endovascular aortic aneurysm repair (EVAR) endoleaks and the need for reintervention are challenging. Additional endovascular treatment is advised for type Ia endoleaks detected on post-EVAR completion angiogram. This study analyzed management and late outcomes of these endoleaks. STUDY DESIGN This was a retrospective review of prospectively collected data from EVAR patients during a 10-year period. All post-EVAR type Ia endoleaks on completion angiogram were identified (group A) and their ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The type 1a endoleak is a well established predictor for aneurysm expansion 5 , and in many cases re-intervention are needed to repair the type 1a endoleak 20 . The odd ratio for expansion of the aneurysm with a type 1a endoleak is 11.5, which was much larger than any other factors, therefore we excluded all seven type 1a endoleak in the following texture analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The type 1a endoleak is a well established predictor for aneurysm expansion 5 , and in many cases re-intervention are needed to repair the type 1a endoleak 20 . The odd ratio for expansion of the aneurysm with a type 1a endoleak is 11.5, which was much larger than any other factors, therefore we excluded all seven type 1a endoleak in the following texture analysis.…”
Section: Resultsmentioning
confidence: 99%
“…When type I endoleaks are identified at the time of the final aortography after EVAR, they are usually considered to justify treatment. 4 Type II endoleaks are mostly benign. However, in a few cases, they can cause enlargement of the sac and can eventually lead to rupture.…”
Section: Discussionmentioning
confidence: 99%
“…3 Endoleaks constitute the main cause of reinterventions. 4 It is often unclear which type of endoleak is the correct diagnose, 5 making the treatment decision difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Each procedure has a high technical success rate, ranging between 89.7% and 100%. AbuRahma et al [34] conducted a study in 71 cases of type Ia endoleak management with a Palmaz/Proximal cuff and found a technical success of 100%. Lu et al [35] found a high success rate in trials of embolization with fibrin glue in 42 cases.…”
Section: T1e Type I Endoleakmentioning
confidence: 99%